2020
DOI: 10.1007/s12182-020-00512-3
|View full text |Cite
|
Sign up to set email alerts
|

3D anatomy and flow dynamics of net-depositional cyclic steps on the world’s largest submarine fan: a joint 3D seismic and numerical approach

Abstract: Supercritical flows are ubiquitous in natural environments; however, there is rare 3D anatomy of their deposits. This study uses high-quality 3D seismic datasets from the world’s largest submarine fan, Bengal Fan, to interpret 3D architectures and flow processes of Pliocene undulating bedforms that were related to supercritical flows. Bengal undulating bedforms as documented in this study were developed in unconfined settings, and are seismically imaged as strike-elongated, crescentic bedforms in plan view and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…Prior studies have recognized the prevalence of crescentic bedforms over a range of subaqueous depositional settings, including delta slopes (Hughes Clarke et al, 2012;Turmel et al, 2015;Hage et al, 2018), the axis of shallow-water submarine channels (Smith et al, 2005;Hughes Clarke et al, 2014;Normandeau et al, 2014Normandeau et al, , 2015, the axis of deep-water channels (Babonneau et al, 2013;Heijnen et al, 2020) and across unconfined submarine fans (Normark et al, 2002;Shao et al, 2021). Recent bathymetric mapping has revealed that the upper sections of submarine channels are often dominated by upslopemigrating crescentic bedforms (Hughes Clarke, 2016;Symons et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have recognized the prevalence of crescentic bedforms over a range of subaqueous depositional settings, including delta slopes (Hughes Clarke et al, 2012;Turmel et al, 2015;Hage et al, 2018), the axis of shallow-water submarine channels (Smith et al, 2005;Hughes Clarke et al, 2014;Normandeau et al, 2014Normandeau et al, , 2015, the axis of deep-water channels (Babonneau et al, 2013;Heijnen et al, 2020) and across unconfined submarine fans (Normark et al, 2002;Shao et al, 2021). Recent bathymetric mapping has revealed that the upper sections of submarine channels are often dominated by upslopemigrating crescentic bedforms (Hughes Clarke, 2016;Symons et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…, 2002; Shao et al . , 2021). Recent bathymetric mapping has revealed that the upper sections of submarine channels are often dominated by upslope‐migrating crescentic bedforms (Hughes Clarke, 2016; Symons et al .…”
Section: Introductionmentioning
confidence: 99%
“…Fielding, 2006; Allen et al ., 2014; Fricke et al ., 2015; Normandeau et al ., 2016; Gall et al ., 2017; Wang & Plink‐Björklund, 2020) to coastal and shallow‐marine (Ventra et al ., 2015; Hughes Clarke, 2016; Kostic et al ., 2019; Slootman et al ., 2019; Di Celma et al ., 2020), to more distal marine settings where sediments are dominantly transported by turbidity currents (e.g. Postma et al ., 2009; Covault et al ., 2014; Symons et al ., 2016; Lang et al ., 2017; Shao et al ., 2021). For a long time, antidunes and corresponding sedimentary structures captured the most attention in supercritical sedimentology, owing to their (as yet partly unresolved) morphodynamic complexities, their potential for palaeohydraulic estimates, and their occurrence in successions originating from both continental and marine environments (e.g.…”
mentioning
confidence: 99%